An Implementation of Web-Based Payroll Information System in Universitas Proklamasi 45 Yogyakarta - Maria Ulfah Siregar; Devara Eko Katon Mahardika (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
Universitas Proklamasi 45 Yogyakarta is a private university which is supervised by a Foundation that has implemented various information systems in various fields of work. However, in the payroll process of the employees are still done manually and have not utilized a computerized system, such as attendance recap, wage recapitulation that is additional salary to basic salary, and the sum of salary received by employees. This makes the payroll process less effective and efficient. This study aims to establish a proposed system that is a web-based information system of employee payroll in the Universitas Proklamasi 45 Yogyakarta with the PHP programming language using Codeigniter Framework and MySQL as its database. The system development method used is the Extreme Programming method. This method was chosen because it promotes intense communication between the client and the system developer so that when there are changes or errors in the system, the developer is always ready to fix it. Extreme Programming also has a simple stage, namely planning, design, coding, and testing. The results of this study are the result of a web-based employee payroll information system that has various actors involved in the management and processing of its data. With this information system, the employee payroll process becomes more effective and efficient, because payroll data is processed and calculated by the system so that it has a high level of data accuracy and does not require a long time in the calculation process.